An animal model study for bone repair with encapsulated differentiated osteoblasts from adipose-derived stem cells in alginate - Shiva Roshankhah (Iranian Journal of Basic Medical Sciences, 2014)
Objective(s): Adipose derived stem cells (ADSCs) can be engineered to express bone specific markers. The aim of this study is to evaluate repairing tibia in animal model with differentiated osteoblasts from autologous ADSCs in alginate scaffold. Materials and Methods: In this study, 6 canine’s ADSCs were encapsulated in alginate and differentiated into osteoblasts. Alkaline phosphatase assay (ALP) and RT-PCR method were applied to confirm the osteogenic induction. Then, encapsulated differentiated cells (group 1) and cell-free alginate (group 2) implanted in defected part of dog's tibia for 4 and 8 weeks. Regenerated tissues and compressive strength of samples were evaluated by histological and Immunohistochemical (IHC) methods and Tensometer Universal Machine. Results: Our results showed that ADSCs were differentiated into osteoblasts in vitro, and type I collagen and osteocalcin genes expression in differentiated osteoblasts was proved by RT-PCR. In group 2, ossification and thickness of trabecula were low compared to group 1, and in both groups woven bone was observed instead of control group's compact bone. Considering time, we found bone trabeculae regression and ossification reduction after 8 weeks compared with 4 weeks in group 2, but in group 1 bone formation was increased in 8 weeks. Presence of differentiated cells caused significantly more compressive strength in comparison with group 2 (P-value ≤0.05). Conclusion: This research showed that engineering bone from differentiated adipose-derived stem cells, encapsulated in alginate can repair tibia defects.